2020
DOI: 10.1101/2020.09.24.311886
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell characterization of transcriptomic heterogeneity in lymphoblastoid cell lines

Abstract: Lymphoblastoid Cell Lines (LCLs) are generated by transforming primary B cells with Epstein-Barr Virus (EBV) and are used extensively as model systems in viral oncology, immunology, and human genetics research. In this study, we characterized single-cell transcriptomic profiles of five LCLs and present a simple discrete-time simulation to explore the influence of stochasticity on LCL clonal evolution. Single-cell RNA sequencing revealed substantial phenotypic heterogeneity within and across LCLs with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…In addition, since LCLs arise after Epstein-Barr viral infection, virus-induced cellular changes due to the transformation process may impact the resulting expression profiles. Single cell RNA sequencing has revealed that LCLs may exhibit substantial phenotypic diversity [ 50 ]. Hence, the variability we observed in the microarray results from three different passages of PR SS and PR control LCLs is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, since LCLs arise after Epstein-Barr viral infection, virus-induced cellular changes due to the transformation process may impact the resulting expression profiles. Single cell RNA sequencing has revealed that LCLs may exhibit substantial phenotypic diversity [ 50 ]. Hence, the variability we observed in the microarray results from three different passages of PR SS and PR control LCLs is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Such populations can comprise individual cells with highly variant phenotypes that fluctuate over time, or rare phenotypes that can be identified in a background of more abundant phenotypes. [18][19][20] Whereas technical capabilities have been developed to capture single-timepoint genetic and transcriptomic profiles of individual cells in a sample, [21][22][23] methods for characterizing single-cell phenotypes in a high-throughput, time-resolved fashion have lagged because of the need to maintain and repeatedly measure the same cell over time. To address this technical gap, Celldom TM recently developed and reported a microfluidic platform that achieves highly parallel single-cell culture.…”
Section: Introductionmentioning
confidence: 99%